Air Pollution from Diesel Particles and Chronic Obstruction Pulmonary Disease - CT Scan Study - Mohammed, Bouzid; Amina, Djadi; H., Guetaf; Boudjema, Bezzazi (European Scientific Journal, ESJ, 2017)
Health problems have been observed in rabbits at low DEP concentration. The subject (animal) showed signs of chronic obstruction pulmonary disease (COPD). CT scan of the biopsy reveals significant emphysematous lesions. DEP grain causes inflammation of lung tissues around sites of deposition. Observations of tissue after formalin fixation reveal brown spots around the points of impact. It also reveals the double organic and inorganic aspect of DEPs. The organic compounds dissolve through slow diffusion in the lung physiological fluid while the inorganic part is partly handled by macrophages (phagocytosis).